Genetic analysis of Karnal bunt (Tilletia indica Mitra) in near isogenic lines of bread wheat (Triticum aestivum L.) - Bala, Ritu; Sharma, Indu; Bains, N S (Journal of Cereal Research, 2011)
Karnal bunt (KB) resistant near isogenic lines (NILs) were  developed using six donor stocks viz., ALDAN ‘ S’ / IAS 58 , CMH 77.308, H567.7I/3*PAR, HD29, HP1531 and W485 in the background of susceptible cultivar WH542. The BC5F2 and BC5F3 populations of six crosses involving these donor stocks with WH542 were screened with a mixture of 17 isolates of T. indica. Genetic analysis in BC5F2 and BC5F3 populations of six crosses revealed involvement of two additive genes in five out of the six crosses viz., WH 542 *5//ALDAN ‘S’ / IAS 58, WH 542 *5/CMH 77.308, WH 542 *5/H567.7I/3*PAR, WH 542 *5/HP1531 and WH 542 *5/W485 whereas 2-3 additive genes for KB resistance wereindicated in WH 542 *5/HD29.